Schistocytic anaemia, severe thrombocytopenia, and renal dysfunction: thrombotic microangiopathy due to severe acquired ADAMTS-13 deficiency - Winkler, A.; Hovinga, J. A. Kremer; Bianchi, V.; Studt, J.-D.; Lämmle, B. (Hämostaseologie, 2003)
We present the case of a woman (age: 64 years) with acute thrombotic microangiopathy due to severe acquired ADAMTS-13 (von Willebrand factor-cleaving protease) deficiency. She was successfully treated with plasma exchange therapy and glucocorticosteroids. She relapsed seven months later, and splenectomy led to lasting remission.Pathomechanisms of thrombotic thrombocytopenic purpura, especially the role of ADAMTS-13, are discussed and therapeutic measures outlined.
Keywords: ADAMTS-13; microangiopathy; thrombotic thrombocytopenic purpura; von Willebrand factor-cleaving protease